Religion in diverse societies crossing the boundaries of prejudice and distrust - Kollontai, Pauline; Yore, Sue 1957- (Routledge, Taylor & Francis Group, 2025)
"Religion in Diverse Societies: Crossing the Boundaries of Prejudice and Distrust contributes to existing cutting-edge research on the constructive contribution religion can make to supporting the promotion of respect, dignity, and justice for all people, considered as essential features in shaping sustainable diverse and peaceful societies. Through a combination of theoretical perspectives, theological analysis, and case studies the diverse contributions examine the role of religion in helping to achieve this and thereby challenge the attitudes and practices which create walls of prejudice and distrust. This timely volume provides a critical discussion of the complex role of religions in the public and political spheres in a range of global contexts and furthers the inter-religious, international, and interdisciplinary understanding of how religion can contribute to promoting and helping create inclusive and diverse societies"--
Keywords: Soziokultureller Wandel; Gerechtigkeit; Religion; Friede; Toleration; Pluralism; Prejudices; Pluralisme (Philosophie); Préjugés; pluralism; religion (discipline)